The object in the museum: some ideas on its semiotic status (2003)
This essay was originally written as a presentation for the seminar titled Museum: history, Memory, Thought (March-May 2003), organied by the Philosophy Department of the Pontificia Universidad Javeriana and the Museo Nacional de Colombia. It describes a fundarnent of museography: the minimum syntax of the object language. After contemplating a definition of museography from the viewpoints of the nature of the objects that are collected the space of the museum, the staging resources and the curator's communicative intentions, the essay proceeds to deal with the pedagogical implications of museography in the context of Umberto Eco 's semiotics. The author analizes some strategies and pedagogical pratices used by the team of the Educational and Cutural Section of the Colombian National Museum.